Analysis of Influence of Temperature on Magnetorheological Fluid and Transmission Performance. (7th July 2015) - Chen, Song; Huang, Jin; Jian, Kailin; Ding, Jun
Abstract : Magnetorheological (MR) fluid shows different performances under different temperature, which causes so many problems like the reduction of rheological properties of MR fluid under a high temperature condition, the uncontrollability of shear stress, and even failure of transmission; on that basis, the influence of temperature on the performance of MR fluid and the cause of the rise in temperature of MR transmission device are analyzed in this paper; the shearing transmission performance of the MR transmission device under the effect of an external magnetic field and the influence of temperature on the shearing stress and transmission performance are analyzed. The study results indicate that temperature highly influences the viscosity of MR fluid, and the viscosity influences the shear stress of the MR fluid. The viscosity of MR fluid gradually declines when temperature rises from 100°C. Once the temperature exceeds 100°C, the viscosity would increase and the temperature stability would decline. Temperature obviously influences the characteristics of MR transmission, and particularly, highly influences the characteristics of MR transmission once being higher than 100°C. The chaining of the material in the magnetic field is influenced, which causes the reduction of the rheological properties, the uncontrollability of the shear stress, and even the failure of transmission.